2007
DOI: 10.1016/j.mcp.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Study of disease-relevant polymorphisms in the TLR4 and TLR9 genes: A novel method applied to the analysis of the Portuguese population

Abstract: Toll-like receptors (TLRs) are cellular receptors that mediate recognition of microbial challenges and the subsequent inflammatory response. Genetic variations within these inflammation-associated genes may alter host-pathogen defence mechanisms affecting susceptibility towards infectious diseases. Taking into account the significance of these genes, we developed a simple and rapid method based in the bi-directional PCR amplification of specific alleles (Bi-PASA) for genotyping known sequence variants in TLR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
1
18
0
2
Order By: Relevance
“…IL-17 expression is related to a third subset of T cells and plays a critical role in the extracellular pathogen response, which may lead to inflammation and is also related to severe autoimmune diseases. 15 In summary, our results indicated that TLR4 gene deficiency keeps DCs in an immature state where they do not express high levels of CD80, CD86, CD40 or MHC-II, and their IL-12 secretion is blocked. This, in turn, leads to reduced CD4 1 T-cell maturation into Th1 phenotypes.…”
Section: To Evaluate the Effects Of Tlr4mentioning
confidence: 55%
See 1 more Smart Citation
“…IL-17 expression is related to a third subset of T cells and plays a critical role in the extracellular pathogen response, which may lead to inflammation and is also related to severe autoimmune diseases. 15 In summary, our results indicated that TLR4 gene deficiency keeps DCs in an immature state where they do not express high levels of CD80, CD86, CD40 or MHC-II, and their IL-12 secretion is blocked. This, in turn, leads to reduced CD4 1 T-cell maturation into Th1 phenotypes.…”
Section: To Evaluate the Effects Of Tlr4mentioning
confidence: 55%
“…14 Other studies have shown the incidence of being a TLR4 Asp299Gly and Thr399Ile carrier (including homozygotes and heterozygotes) worldwide lies in the range of 2.5%-20.7%. [15][16][17][18][19] The TLR4 Asp299Gly polymorphism, in particular, is the highest in African Americans, while in a western Iran population, the highest incidence for a mutation was found for the TLR4 Thr399Ile polymorphism, which is in, contrast, very rare in Asian populations, such as those in Japan and South Korea. 20,21 Carriers of the Thr399Ile TLR4 gene mutation have a significantly increased risk of developing GVHD, 42% versus 15% of non-affected patients, whereas transplant-related mortality, overall survival rate and the incidence of infectious complications are not influenced by the mutated gene.…”
Section: Introductionmentioning
confidence: 98%
“…The population studies have revealed a speciWc geographical (ethnic) distribution of the TLR4 Asp299Gly and (or) Thr399Ile haplotypes. The African have the highest frequency of these two polymorphisms of about 16% [26], followed by Caucasian White with the frequency of 4-10% [27][28][29][30][31][32][33], and Asian populations show a complete absence of Asp299Gly and Thr399Ile. Our study, together with reports from other authors, suggests a possibility that these two polymorphisms, widely reported in African and Caucasians, do not occur among Asian populations.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 Genotyping was performed using bidirectional polymerase chain reaction (PCR) amplification of specific alleles (Bi-PASA), as previously described. 18 The PCR primers used were as follows: P1, GTAGTCCCAGCTACTTGAGG; P2, ACCACTTGAGAT-TCACAACA; P3, ggcggcggggAGTGTGCCCTCATAT; and P4, gggccgggggTTCTTCTCACAAATACTC. Allele and genotype frequencies of the DECTIN1 Y238X polymorphism were similar to those observed in the National Center for Biotechnology Information database and comparable between donors and recipients (data not shown).…”
Section: Genetic Screening Of the Dectin1 Y238x Polymorphismmentioning
confidence: 99%